A impenhorabilidade dos bens declarados por ato voluntário na hipótese do artigo 833, inciso I do código de processo civil - Secchin, Rodrigo Ferrari (2023)
This study aims to decipher the legal contours of assets that cannot be seized by a voluntary act under the terms of item I of article 833 of the Code of Civil Procedure. Therefore, it is necessary to answer the following question: what is the limitation of property liability for assets declared, by voluntary act, not subject to execution in order to apply the terms of the aforementioned provision? The rules on the unseizability of assets, provided for in the Brazilian legal system, aim to protect and safeguard some rights of the person responsible and their family, such as the right to subsistence and housing. However, the rules on unseizability have recently become a topic of debate and discussion among legal scholars and practitioners. Particularly this hypothesis of “limitation” of property liability has not received the attention it deserves, with no specific academic work on it, despite a series of questions that arise from it. The main objectives of this dissertation were, with a view to answering the initial question above, to analyze the foundations and principles that support the unseizability of assets and their importance for guaranteeing fundamental rights, verifying the reasons that justify the political limits of civil and , therefore, identify the criteria and requirements for its application, with the aim of proposing solutions and suggestions to improve the interpretation and application of the legal provision in question, with the aim of guaranteeing the protection of fundamental values and the effectiveness of the provision jurisdictional. It is intended that this academic work contributes to the debate and reflection on the unseizability of assets, especially with regard to those declared by voluntary act, provided for in article 833, item I of the Brazilian Code of Civil Procedure, offering subsidies for an interpretation adequate and considered standard in light of fundamental values and legal certainty. Furthermore, it is hoped that the results and suggestions presented can help promote more effective and equitable justice for Brazilian society.